Encounters with coloniality: Students’ experiences of transitions from rural contexts into higher education in South Africa - Timmis, Sue; Mgqwashu, Emmanuel Mfanafuthi; Naidoo, Kibbie; Muhuro, Patricia; Trahar, Sheila; Lucas, Lisa; Wisker, Gina; de Wet, Thea (Critical Studies in Teaching and Learning, 2023)
This paper makes visible the experiences of students transitioning to higher education from rural communities and backgrounds in South Africa. In line with decolonial perspectives, the research adopted a participatory methodology that involved students as co-researchers. We argue that there is a lack of recognition of students from rural contexts, and their potential to re-shape higher education. We highlight their challenges of applying, entering and participating in universities and the loss of agency experienced. We then show how they found new agentic possibilities by analysing the cultural capital, practices, and local knowledges that students bring into the university space, and the improvisations they make to negotiate challenges. We argue that to re-shape higher education and transform curricula, institutions need to bring multiple knowledges into dialogue through a transformation process that links places, people, knowledge(s), and skills, offering students spaces for recognition and visibility to make sense of their own experiences.